Tree species composition of 0.1 ha plot at UiTM Jengka education forest (line 15) - Mustamin, Muliadi; Ismail, Nur Isfarina; Muda, Norhayati; Mohamad, Munirah (2012)
This study was conducted to determine the species composition and density of trees in the UiTM Jengka Education Forest at Line 15. A plot size of 20m x 50m survey has been created at randomly at Line 15 and all trees with a diameter at breast height (OBH) 5cm and above were measured, marked, recorded and identified. A total of 159 individual trees were measured in which consists of 88 species, 63 genera of 31 families. Compared to Turner (1995), the number of species, genera and families that are present in the study area was only 1.06% species, 3.76% genera and 12.50% families from the plant checklist of Peninsular Malaysia. Euphorbiaceae was a families that has a largest number of species and genera with 25 species and nine genera. Burseraceae was recorded as a family with the highest number of individual which represented 25 individual, followed by Euphorbiaceae with 22 individuals. Artocarpus and Shorea are genera with the highest number of species which is 5 5.68% from the total species and followed by Aglaia, Aporosa, Canarium and Santiria for the each recorded 3 (3.40%). With the highest number of nine individuals, Artocarpus, Canarium and Santiria the genera that have the highest number of individuals. Buchanania sessifolia was a species having the highest individual total of 159 found in the study area. There are five (5.70%) endemic species in Peninsular Malaysia recorded in this study plot. The density of 5cm tree diameter at breast height (DBH) and above in the study area are 159 individuals/ 0.1 ha or 1590 individuals/ha. Burseraceae was a families with the highest individuals total of 250 individuals/ha. Artocarpus, Canarium and Santiria was the genera with the highest individual total of 90 individuals/ha. Buchanania sessifolia the species with the highest individual total of 70 individuals/ha. The community structure for the tree that has reached ≥ 15 cm DBH in UiTM Jengka Education Forest at Line 15 was 77.36% from the total number of individual recorded.